ATRT-29. SUCCESS OF HIGH DOSE CHEMOTHERAPY IN INFANTS PRESENTING WITH ATYPICAL TERATOID RHABDOID TUMOURS (ATRT). Issue 2 (22nd June 2018) - O'Hare, Patricia; Jorgensen, Mette; Michalski, Anthony; Slater, Olga; Phipps, Kim; Aquilina, Kristian; Jeelani, Owaase; Chang, Yen-Ch'ing; Gains, Jenny; Fairchild, Amy; Pickles, Jess; Jacques, Thomas; et al.
Abstract: BACKGROUND: ATRT is an aggressive tumour of infancy with a historically poor prognosis. In very young patients radiotherapy is avoided due to neurocognitive toxicity, however high dose chemotherapy (HDC) is used as an alternative treatment strategy in this group of patients. METHODS: This is a retrospective review of 30 patients diagnosed with ATRT from 2009–2016, 24 of whom received adjuvant treatment. 5 received radiotherapy upfront, of whom 3 remain alive. 19 patients received adjuvant chemotherapy (median age at diagnosis 10 months, 38% with germline mutation). RESULTS: 6/19 patients didn't proceed to HDC. One patient progressed and was salvaged with radiotherapy and remains alive. The other 5 patients progressed on chemotherapy after 5, 6 (n=3) or 9 cycles of treatment. 13 patients proceeded to HDC (of whom 8 remain alive). 5 patients achieved gross total resection with surgery, 4 of whom remain alive post HDC. A further 2 patients, who had subtotal resection at diagnosis, achieved CR prior to commencing HDC, and both of these patients are alive. Of the remaining 6 patients who received HDC, one patient achieved CR only after HDC but is disease free 40 months post HDC. A further patient who relapsed within 6 months of HDC was salvaged with focal radiotherapy and remains in remission with 18 months of follow up. Treatment related mortality is 15%. CONCLUSION: HDC offers significant chance of prolonged survival for infants with ATRT, without the need for radiotherapy. CR achieved either with surgery or chemotherapy is an important prognostic factor.